Selective Export into Extracellular Vesicles and Function of tRNA Fragments during T Cell Activation - Ni-Ting Chiou; Robin Kageyama; K. Mark Ansel (Cell Reports, 2018)
Summary: The discovery of microRNA (miRNA) sorting into extracellular vesicles (EVs) revealed a novel mode of intercellular communication and uncovered a link between cellular endomembrane compartments and small RNAs in EV-secreting cells. Using a two-step ultracentrifugation procedure to isolate EVs released by T cells, we found that 45% of tRNA fragments (tRFs), but fewer than 1% of miRNAs, were significantly enriched in EVs compared with the corresponding cellular RNA. T cell activation induced the EV-mediated release of a specific set of tRFs derived from the 5′ end and 3′-internal region of tRNAs without variable loops. Inhibition of EV biogenesis pathways specifically led to the accumulation of these activation-induced EV-enriched tRFs within multivesicular bodies (MVBs). Introducing antisense oligonucleotides to inhibit these tRFs enhanced T cell activation. Taken together, these results demonstrate that T cells selectively release tRFs into EVs via MVBs and suggest that this process may remove tRFs that repress immune activation. : Chiou et al. show that T cells release extracellular vesicles that carry RNA cargo enriched in tRNA fragments. Immune activating signals enhance multivesicular body formation and the secretion of vesicles containing specific tRNA fragments. Within cells, these tRNA fragments inhibit T cell activation and cytokine production. Keywords: tRNA fragment, tsRNA, extracellular vesicle, exosome, T lymphocyte